The lucky few : finding God's best in the most unlikely places - Avis, Heather (Zondervan, 2017)
"What happens when life doesn't turn out like you planned? Mother of three adopted children--two with Down syndrome--Heather Avis learned that it's truly the lucky few that recognize God's plan is best, even when it is radically different from the plan we have ourselves. Your life may be uncomfortable and messy but you can be among the lucky few" -- provided by publisher.